Application Of The Acmeological Approach To Improve The Efficiency Of The Professional Educational Process (Journal of Pharmaceutical Negative Results, 2023)
This article discusses the development of a methodology for increasing the effectiveness of the educational process based on the acmeological approach in vocational education and the development of the process of preparing for professions by using acmetechnology, computer technology, and it also provides for obtaining a professional acme personality who owns professional abilities, orientation and competence as a result of using forms and methods of organizing vocational education and training; creating pedagogical and psychological conditions for this, establishing professionally oriented training, productive use of modern educational and information technologies based on acmeological orientation - acmeological education and training, acmeological approach, technologies aimed at personality development.Scientifically based on the development of theoretical and practical foundations for improving the process of training students in professional colleges, improving the optimal personality development in adolescence and youth on the basis of the acmeological approach is one of the important factors and, it is justified that the education of self-thinking, with high intellectual and spiritual potential of youth, not inferior to its peers in any field on a global scale, the need to develop its ability for logical, independent, active creative thinking, increase the level of individual professional formation, solve them with the help of a wide practical application of factors (conditions, forms, methods and means), activating education, improving on the basis of the acmeological approach to preparing for professional activities of students in vocational colleges determines the relevance of the research topic.The development of science and technology at the international level, advanced production experience, changes taking place in society and nature, which are intensively entering into practice, require the improvement of pedagogical and psychological mechanisms for training specialists in vocational education. At the same time, it is important to carry out intensive training, ensure the integration of pedagogical, psychological, and acmeological functions of education, develop methods of acmeological vocational guidance in the educational process. Such an approach to improving the educational environment on the basis of the acmeological approach makes it possible to form a specialist, who is amenity, develop vocational training, create scientific and methodological support, improve the quality of training of specialists, which determines the relevance of the topic of this article.